2022
DOI: 10.3389/fnins.2022.1038945
|View full text |Cite
|
Sign up to set email alerts
|

The autonomic nervous system: A potential link to the efficacy of acupuncture

Abstract: The autonomic nervous system (ANS) is a diffuse network that regulates physiological systems to maintain body homeostasis by integrating inputs from the internal and external environment, including the sympathetic, parasympathetic, and enteric nervous systems (ENS). Recent evidence suggests that ANS is one of the key neural pathways for acupuncture signal transduction, which has attracted worldwide attention in the acupuncture field. Here, we reviewed the basic and clinical research published in PubMed over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…[ 25 ] Alterations in the central autonomic network or destruction of autonomic system pathways from the hypothalamus to the brain stem may lead to ANS dysfunction. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Alterations in the central autonomic network or destruction of autonomic system pathways from the hypothalamus to the brain stem may lead to ANS dysfunction. [ 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…The autonomous nervous system (ANS) is essential in maintaining the stability of the organism. It is composed mainly of the sympathetic and parasympathetic nerves and plays a significant role in acupuncture’s therapeutic effects on gastrointestinal motility, inflammation, analgesic anesthesia,and more ( 84 ). However, recent studies have demonstrated that acupuncture’s autonomic regulation is not as straightforward as that of the sympathetic or parasympathetic pathways.…”
Section: Somatosensory-autonomic Reflex To Modulate the Immune Responsementioning
confidence: 99%
“…Limbic systems such as the IC and ACC are essential for the regulation of painful emotions. These autonomic cortical regions form a complex pain regulatory network with autonomic nuclei related to descending inhibition systems, such as the PAG, NTS, RVLM, and dorsal reticular nucleus, to participate in acupuncture analgesia and alleviate pain-related emotions [104] . Several studies have shown that EA can reduce sympathoexcitatory responses, in part, through its effect on multiple brain regions, such as the arcuate nucleus in the hypothalamus, PAG, and RVLM and raphe nuclei in the brainstem, among others [105][106][107] .…”
Section: Acupuncture Acts On the Brain Areas Of Pain And The Sympathe...mentioning
confidence: 99%